The Iron Chelators Dp44mT and DFO Inhibit TGF-β-induced Epithelial-Mesenchymal Transition via Up-Regulation of N-Myc Downstream-regulated Gene 1 (NDRG1) - Chen, Zhiqiang (American Society for Biochemistry and Molecular Biology, 2012)
The epithelial-mesenchymal transition (EMT) is a key step for cancer cell migration, invasion, and metastasis. Transforming growth factor-β (TGF-β) regulates the EMT and the metastasis suppressor gene, N-myc downstream-regulated gene-1 (NDRG1), could play a role in regulating the TGF-β pathway. NDRG1 expression is markedly increased after chelator-mediated iron depletion via hypoxia-inducible factor 1α-dependent and independent pathways (Le, N. T. and Richardson, D. R. (2004) Blood 104, 2967–2975). Moreover, novel iron chelators show marked and selective anti-tumor activity and are a potential new class of anti-metabolites. Considering this, the current study investigated the relationship between NDRG1 and the EMT to examine if iron chelators can inhibit the EMT via NDRG1 up-regulation. We demonstrated that TGF-β induces the EMT in HT29 and DU145 cells. Further, the chelators, desferrioxamine (DFO) and di-2-pyridylketone-4,4-dimethyl-3-thiosemicarbazone (Dp44mT), inhibited the TGF-β-induced EMT by maintaining E-cadherin and β-catenin, at the cell membrane. We then established stable clones with NDRG1 overexpression and knock-down in HT29 and DU145 cells. These data showed that NDRG1 overexpression maintained membrane E-cadherin and β-catenin and inhibited TGF-β-stimulated cell migration and invasion. Conversely, NDRG1 knock-down caused morphological changes from an epithelial- to fibroblastic-like phenotype and also increased migration and invasion, demonstrating NDRG1 knockdown induced the EMT and enhanced TGF-β effects. We also investigated the mechanisms involved and showed the TGF-β/SMAD and Wnt pathways were implicated in NDRG1 regulation of E-cadherin and β-catenin expression and translocation. This study demonstrates that chelators inhibit the TGF-β-induced EMT via a process consistent with NDRG1 up-regulation and elucidates the mechanism of their activity.